Earth-abundant and environmentally benign Ni–Zn iron oxide intercalated in a polyaniline based nanohybrid as an ultrafast photodetector. Issue 20 (9th May 2022) - Singh, Anshika; Verma, Arpit; Yadav, B. C.; Chauhan, Pratima
Abstract : Nickel–zinc iron oxide (NZF) was introduced into a polyaniline (PANI) matrix by an in-situ chemical oxidation polymerization approach. This nanohybrid was used to fabricate a photodetector device on a biodegradable and flexible paper substrate. Abstract : Nickel–zinc iron oxide (NZF) was introduced into a polyaniline (PANI) matrix by an in situ chemical oxidation polymerization approach. The surface composition and chemical states were investigated by X-ray photoelectron spectroscopy (XPS), which revealed an Fe 2p spectrum with the two peak positions of Fe 2p3/2 and Fe 2p1/2 at 711.00 and 724.48 eV, respectively. Deconvolution of the Fe 2p3/2 peak revealed two components with binding energies of 713.98 and 718.16 eV, corresponding to the presence of Fe cations in the octahedral and tetrahedral sites. Additionally, the Rietveld refinement of NZF showed a cubic system with the Fd 3 m space group. High-resolution transmission electron microscopy (HRTEM) analysis showed that the NZF material strongly interacts with polyaniline, while the selected area electron diffraction (SAED) pattern perfectly matched with the XRD data. Lognormal distribution was used to determine the particle size, which was found to be in the range of 1–100 nm. A flexible photodetector device utilizing the NZF–PANI nanohybrid was fabricated on an environmentally friendly, biodegradable cellulose paper substrate and the device exhibited excellent performance, i.e., a responsivity of 0.069 A W −1 and detectivity of 7.258 × 10 10 Jones at a very low voltage of 0.1 V. The non-stretched device showed a responsivity of 24.980 A W −1 at 5 V, whereas at 2 cm −1 bending curvature, the device showed a responsivity of 20.175 A W −1, which was much higher than the responsivity of a commercial photodetector (<0.5 A W −1 ).